Analisis produktivitas alat penangkapan gurita yang dioperasikan menggunakan umpan tiruan: Productivity analysis of octopus fishing gear operated using artificial bait - Ayu Suciati; Muhammad Kurnia; M. Abduh Ibnu Hajar; Alfa Filep Petrus Nelwan; Ilham Jaya; Najamuddin Najamuddin (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2024)
The objective of this study is to ascertain the differences in catches of octopus fishing, as well as to determine the productivity of octopus fishing gear using bole-bole and pocong-pocong. This research was conducted in October and November 2023 in the waters of Langkai Island and Lanjukang Island, Makassar City. The methodology employed in this research is a case study. Primary data were collected directly by following, recording, and identifying the number of catches, the size of the catch, and the length of time to operate the fishing gear. The data were then analysed using the T-test to determine the difference in catches on octopus fishing rods using bole-bole and pocong-pocong. The results of the study during 31 trips yielded a total of 92 fish. The catch of pocong-pocong is more likely to result in the capture of an octopus, with a value of 59% of octopus caught compared to bole-bole, which is 41% of the total hauling of 218 times. The pocong-pocong had a higher productivity with an average value of 57.81 grams per minute compared to bole-bole with an average value of 47.29 grams per minute during 31 fishing trips. The results of the statistical analysis using the T-test demonstrated that there were differences in the catches between the two fishing gears. The pocong-pocong had a higher catch than bole-bole.